A Clockwork Orange - Anthony Burgees (London Penguin Books Ltd, 2011)
A Clockwork Orange, novel by Anthony Burgess, published in 1962. Set in a dismal dystopian England, it is the first-person account of a juvenile delinquent who undergoes state-sponsored psychological rehabilitation for his aberrant behaviour.
Keywords: Dystopian fiction